2017
DOI: 10.1002/chem.201704381
|View full text |Cite
|
Sign up to set email alerts
|

An FeIII Azamacrocyclic Complex as a pH‐Tunable Catholyte and Anolyte for Redox‐Flow Battery Applications

Abstract: A reversible Fe /Fe redox couple of an azamacrocyclic complex is evaluated as an electrolyte with a pH-tunable potential range for aqueous redox-flow batteries (RFBs). The Fe complex is formed by 1,4,7-triazacyclononane (TACN) appended with three 2-methyl-imidazole donors, denoted as Fe(Tim). This complex exhibits pH-sensitive redox couples that span E (Fe /Fe )=317 to -270 mV vs. NHE at pH 3.3 and pH 12.8, respectively. The 590 mV shift in potential and kinetic inertness are driven by ionization of the imidaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
6
31
0
Order By: Relevance
“…The energy density is 8.4 mWh/L for the whole cell, which is too low for real-world applications, but is similar to that of other exploratory work that examined aqueous symmetric metal-ligand complexes, such as the 1 mM (aq) iron triazametallocycle-based RFB mentioned in the introduction, which has an energy density of 7.0 mWh/L. 27 Moreover, as shown in Figure S9, there was a negligible change in the colour of the membrane after 100 cycles. As seen in Figure 6a where ?…”
Section: Figure 1 (A)supporting
confidence: 68%
See 1 more Smart Citation
“…The energy density is 8.4 mWh/L for the whole cell, which is too low for real-world applications, but is similar to that of other exploratory work that examined aqueous symmetric metal-ligand complexes, such as the 1 mM (aq) iron triazametallocycle-based RFB mentioned in the introduction, which has an energy density of 7.0 mWh/L. 27 Moreover, as shown in Figure S9, there was a negligible change in the colour of the membrane after 100 cycles. As seen in Figure 6a where ?…”
Section: Figure 1 (A)supporting
confidence: 68%
“…26 An elegant study of a triazametallocycle iron complex with pH-dependent oxidation states has demonstrated applicability as a posolyte at low pH, and a negolyte at high pH, and thus could serve as a symmetrical aqueous RFB, albeit with different pH values on opposite sides of the membrane. 27 In addition, a handful of examples of organic and polymerbased aqueous symmetric batteries have been tested, and include a combi-molecules comprising tethered negolyte-posolyte combinations of TEMPO and phenazine, 28 and TEMPO and viologen. 29 In this work we explore the properties and utility of a water soluble version of a bis(pyridine-2,6-diimine) cobalt(II) complex for aqueous symmetric RFB applications ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This pH‐dependence is due to the proton‐coupled electron‐transfer (PCET) involved in the redox chemistry of MB. Active species that invoke PCET redox chemistry have been previously observed in a handful of other molecules, the most notable being quinones ,. This pH tunability can serve as the basis for enhancing cell voltages by shifting the E 1/2 values .…”
Section: Resultsmentioning
confidence: 86%
“…The total charge of the Ru complex is omitted. of using a PCET system in this way had been implemented with organic quinone derivatives, [52] but its scope was extended to redox-flow batteries by using a pHtunable Fe(III) azamacrocyclic complex as both the catholyte and anolyte based on the multiple protonated forms of the Fe complex [53].…”
Section: Figure 11mentioning
confidence: 99%